Representaciones del cuerpo en la era de la tecnociencia. Una reflexión ética (2023)
Three things are analyzed in this text. First, the formation of the machine-body of the modern world, it means, the modeling of the existence according to a technologic rationality wangled and administered by modern institutions like the family, the school, the job and the clinic. Second, the implantation in the life of subject-object dualism, matter which will be administered and initiated by medicine and scientific technical reason, main pillars of the modern age. Culturally the humankind will have an antagonistic relationship with the things, the nature and the others. With this, it will be established a vertical relationship with "world of life" where really important is the control, manipulation, the domain and the maintenance of order trough the technique. Finally, it becomes evident the ethic problem which comes out before the establishment of a way of rationality that covers up, hide and changes the existing of that "vital world".